2018
DOI: 10.1007/s10637-017-0558-5
|View full text |Cite|
|
Sign up to set email alerts
|

Sphingadienes show therapeutic efficacy in neuroblastoma in vitro and in vivo by targeting the AKT signaling pathway

Abstract: Neuroblastoma is a childhood malignancy that accounts for approximately 15% of childhood cancer deaths. Only 20–35% of children with metastatic neuroblastoma survive with standard therapy. Identification of more effective therapies is essential to improving the outcome of children with high-stage disease. Sphingadienes (SD) are growth-inhibitory sphingolipids found in natural sources including soy. They exhibit chemopreventive activity in mouse models of colon cancer, where they mediate cytotoxicity by inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…However, there are in vivo results suggesting that YAP, Akt and p27 kip1 are related to neuroblastoma. 13,22,66 YAP is significantly higher in the malignant neuroblastoma tissues of human, compared to the peritumoral tissues. 13 Inhibition of the Akt signalling pathway shows therapeutic efficacy in neuroblastoma xenografts in vivo.…”
Section: Discussionmentioning
confidence: 91%
“…However, there are in vivo results suggesting that YAP, Akt and p27 kip1 are related to neuroblastoma. 13,22,66 YAP is significantly higher in the malignant neuroblastoma tissues of human, compared to the peritumoral tissues. 13 Inhibition of the Akt signalling pathway shows therapeutic efficacy in neuroblastoma xenografts in vivo.…”
Section: Discussionmentioning
confidence: 91%
“…Our data extends this work by demonstrating that sphingadiene-containing lipids are more slowly catabolized than sphingosine-containing lipids in living cells. Similarly, S1P lyase mutants in the fly Drosophila melanogaster accumulate sphinga-4,6-diene (54), which is speculated to contribute to muscle degeneration (40). In agreement with our data, Jojima et al (39) also found that both SphK1 and SphK2 catalyse sphingadiene phosphorylation as efficiently as sphingosine.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring sphingadienes inhibit both chemically-and genetically-induced colon cancer development in mice (51)(52)(53), associated with disrupted Akt membrane translocation and signaling (53), and reduced Wnt transcriptional activity (52). Sphingadienes have also been shown to suppress the growth of neuroblastoma xenograft tumors (54).…”
Section: Discussionmentioning
confidence: 99%
“…Findings with CoQ 10 reported herein extend the repertoire of hydrophobic bioactive agents to be successfully incorporated into ND (Ryan, 2010). For example, the polyene antibiotic, amphotericin B (Oda et al, 2006), the polyphenol phytonutrient, curcumin (Ghosh et al, 2011), the bioactive sphingolipid, sphingadiene (Zhao et al, 2018), contrast agents for medical diagnostics (Kornmueller et al, 2019), and the cholesterol synthesis inhibitor, simvastatin (Duivenvoorden et al, 2014), have been formulated into ND and characterized in terms of their biological activity. In general, hydrophobic bioactive agent incorporation into ND results in retention, if not enhancement, of biological activity.…”
Section: Introductionmentioning
confidence: 99%